On the Utilization of Social Animals as a Model for Social Robotics - Miklósi, Ádám; Gácsi, Márta (Frontiers in Psychology, 2012)
Social robotics is becoming a driving field in building artificial agents. The possibility to construct agents that can engage in meaningful social interaction with humans presents new challenges for the engineers. In general social robotics has been inspired dominantly by human psychology and aimed for building human-like robots. Only a small subcategory of “companion robots” (also referred to as robotic pets) was build to mimic animals. In the opinion essay we argue that all social robots should be seen as companions and more conceptual emphasis should be put on the inter-specific interaction between humans and social robots. This view is underlined by the means of an ethological analysis, and critical evaluation of present day companion robots. We suggest that human-animal interaction provides a rich source of knowledge for designing social robots that are able to interact with humans under a wide range of conditions.